(untitled) (ModaPalavra e-periódico, 2022)
The production of clothing has several operational steps, such as industrial sewing, which is used on textile surfaces as a materialization resource, that is, the union of two or more layers of fabrics by sewing points that makes the object tridimensional. In this context, the research seeks to explore the possibilities of industrial sewing to be considered as a creative resource to generate innovative surfaces in clothing, anchored on three pillars: in the design approaches of Surface Design, in the technical aspects of industrial sewing and in characteristics of materials textiles. For this, an exploratory investigation was carried out, with application of experiments using four straight industrial sewing techniques in three grammages of fabrics. The results were categorized through the effects obtained on the surfaces as graphic, structural and graphic structural function, demonstrating to be a creative resource that can be explored at the beginning of the design of clothing products.